Dasar Wajib Patuh pada Undang-Undang Perkawinan - Niken Retno Wulandari (Majelis: Jurnal Hukum Indonesia, 2025)
This study discusses the basis of Indonesian society’s obligation to comply with the Marriage Law (UUP) as a manifestation of obedience to both state law and religious teachings. The study arises from the reality that, despite the UUP and the Compilation of Islamic Law (KHI) serving as the legal foundation for marriage in Indonesia, many still violate its provisions, such as through unregistered (siri) marriages. Using a normative juridical approach and qualitative descriptive analysis, this research examines the juridical, philosophical, and sociological foundations of legal obedience to the UUP and its implications for family and social life. The findings show that juridically, obedience to the UUP is grounded in the principle of legality and state sovereignty; philosophically, it reflects the values of Divinity and Humanity embodied in Pancasila; and sociologically, it functions as social engineering to protect women and children while ensuring social order. Compliance with the UUP therefore holds not only legal but also moral and spiritual significance, serving as a means to achieve harmonious families, social order, and a just nation.